Pulmonary arteriovenous malformations: evidence of physician under-education. Issue 2 (12th April 2017) - Shovlin, Claire L.; Gossage, James R.
Pulmonary arteriovenous malformations (PAVMs) are abnormal blood vessels that connect pulmonary arteries direct to pulmonary veins, thus bypassing the pulmonary capillaries which are essential to filter, process and oxygenate blood [1]. Population-wide screening programmes using thoracic computed tomography scans suggest a prevalence of 1 in 2630 (95% CI 1 in 1315–1 in 5555) [2], although the condition is subject to substantial under-ascertainment [3]. PAVMs pose unique management challenges; publication patterns indicate their importance remains poorly recognised http://ow.ly/7iIT304WYl2